Influence of Work-Family Conflict and Organizational Climate in Managing Work Stress - Rahman, Reezlin Bin; Isa, Zainab Binti; Aznan, Dan Eni Binti (Archives of Business Research, 2022)
Stress management requires good management to deal with it. A person's ability to manage stress when facing stress requires a skill. Work environment conditions and work-family conflicts require person learn to deal with the stress. This study aims to see to what extent Work Family conflict and Organizational Climate influence Stress Management. The study conducted on 35 respondents at a Technical and Vocational Education institution through quantitative data collection as a case study is to find out what factors influence in managing the stress of the staff. Data analysis is using SPSS have found interesting findings. The results of the study based on objectives have shown that work-family conflict affects stress management more compared to organizational climate affecting stress management.